Historical Narratives and Spatial Strategies of Reappropriation in Three Romanian Orthodox Monasteries - Tateo, Giuseppe; Cozma, Ioan; Massenz, Giulia (Fieldwork in Religion, 2024)
Contrary to the abundance of shared religious places throughout south-eastern Europe, multi-religious interaction is not a regular feature in Romania. Pilgrimages and visits to the popular Orthodox monasteries of Prislop and Nicula in Transylvania and Dervent in Dobruja are an exception to this trend. Unsurprisingly, these two regions are historically characterized by a remarkable ethnic and religious diversity. The two Transylvanian monasteries attract practitioners of different Christian denominations (Orthodox, Greek-Catholic, Roman-Catholic and Evangelical), while Dervent is a devotional site for Christians and Muslims (Tatars, Turks and Roma) alike. Common to all three monasteries is the presence of allegedly miracle-working objects, artefacts and bodies: a stone cross at Dervent, the Virgin Mary icon at Nicula, and the tomb of the charismatic monk Arsenie Boca at Prislop, respectively. Based on ethnographic fieldwork conducted in the three monasteries during both important feasts and everyday monastic life, this article is a multidisciplinary exploration of the workings of inter-religious competition, sharing and interaction. It combines the methods typical of ethnographic research with observations on how the religious space is navigated and socialized through the support of cartography and archival satellite images. The article casts light on how the historical narratives and spatial strategies enacted by the Romanian Orthodox Church overlap in the attempt to reclaim legitimate ownership and exclusive primacy over three popular devotional sites with a composite ethnic and religious past.